The Relationship between Amount of Computer Usage and Computer Vision Syndrome in Sinarmas Bank Employees - Zukhri, Monica Fradisha; Wulandari, R AJ Sri; Ayusari, Amelya Augusthina (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Background: Nowadays, in this technological era, prolonged uses of computer could result in increasing incidence rate of computer vision syndrome, particularly to people who work at computers. Computer vision syndrome is a complex ocular problems that translates to discomfort feeling on eyes due to high visual demands of computer viewing. Hence, this study aim to know the relationship between amount of computer usage and computer vision syndrome. Methods: An analytical observational cross sectional study was conducted involving Sinarmas Bank employees. Subjects were collected using purposive sampling method, based on inclusive and exclusive criteria. Data regarding computer vision syndrome were obtained using a questionnaire. The collected data were analyzed with Chi-square test followed by Coefficient Contingency test. Result: This study revealed that 29 subjects (46.0 %) who used computer for more than 4 hours experienced computer vision syndrome, while subjects who used computer for 2-4 hours and less than 2 hours did not show computer vision syndrome. Significance value of the relationship between amount of computer usage and computer vision syndrome in Sinarmas Bank employees shown by Chi square test was p=0.000. Hence, there was significant association between the variables. Coefficient contingency test result also demonstrated that there wasÂ a strong association between amount of computer usage and computer vision syndrome in Sinarmas Bank employees (c=0.707). Conclusion: This study statistically stated that there is a significant relationship between amount of computer usage and computer vision syndrome in Sinarmas Bank employees. Keywords: Computer Vision Syndrome, Amount of Computer Usage.Â